Sturge-Weber syndrome Case report - Witanowska, Joanna; Laskowska, Małgorzata; Zadurska, Małgorzata (Forum Ortodontyczne / Orthodontic Forum, 2018)
Sturge-Weber Syndrome (SWS – encephalotrigeminal angiomatosis) is a rare non-hereditary congenital condition. It develops in the early foetal period, at the stage when the embryo head is being formed, as a result of a random somatic mutation of the GNAQ gene due to unknown reasons. The main symptom is the formation of congenital angiomas, especially in the area of capillaries, in the leptomeninges in the brain, and along the course of the trigeminal nerve. Such angiomas may also be present on lips, and in the whole oral cavity: on its bottom, palate and gingivae. It may lead to serious malocclusions and breathing problems. Aim. This article aims to present problems regarding orthodontic treatment of patients with Sturge-Weber syndrome, using an example of a 7-year-old female patient. Case report. A 7-year-old girl with all signs of this syndrome, namely glaucoma, epilepsy, neurological disorders, cutis marmorata telangiectatica congenita and after sanitation of the oral cavity, had hygiene procedures and exercises with a vestibular plate introduced. Two attempts to take impressions for appliances failed due to patient’s anxiety reactions. Conclusions. This case shows difficulties that may be faced by an orthodontist when treating patients with Sturge-Weber syndrome. In this case, namely type I in the Roach scale, due to neurological disorders it was necessary to take special precautions in relation to procedures introduced and to avoid stress in a patient. It makes orthodontic treatment difficult. (Witanowska J, Laskowska M, Zadurska M. Sturge-Weber syndrome. Case report. Orthod Forum 2018; 14: 143-9)